Novel selective β1-adrenoceptor antagonists for concomitant cardiovascular and respiratory disease - Baker, Jillian G.; Gardiner, Sheila M.; Woolard, Jeanette; Fromont, Christophe; Jadhav, Gopal P.; Mistry, Shailesh N.; Thompson, Kevin S.J.; Kellam, Barrie; Hill, Stephen J.; Fischer, Peter M. (Federation of American Society of Experimental Biology, 2017)
β-Blockers reduce mortality and improve symptoms in people with heart disease. However, current clinically available β-blockers have poor selectivity for the cardiac β1-adrenoceptor (AR) over the lung β2-AR. Unwanted β2-blockade risks causing life-threatening bronchospasm and a reduction in the efficacy of β2-agonist emergency rescue therapy. Thus current life-prolonging β-blockers are contraindicated in people with both heart disease and asthma. Here we describe NDD-713 and NDD-825, novel highly β1-selective neutral antagonists with good pharmaceutical properties that can potentially overcome this limitation. Radioligand binding studies and functional assays using human receptors expressed in CHO cells demonstrate that NDD-713 and NDD-825 have nanomolar β1-AR affinity, greater than 500-fold β1-AR vs β2-AR selectivity and no agonism. Studies in conscious rats demonstrated that they are orally bioavailable and cause pronounced β1-mediated reduction of heart rate while showing no effect on β2-mediated hindquarters vasodilatation. The compounds also have good disposition properties and show no adverse toxicological effects. They potentially offer a truly cardioselective β-blocker therapy for the large number of people with heart and respiratory, or peripheral vascular comorbidities.